Frutos de juá (Ziziphus joazeiro Mart.): caracterização química, nutricional, bioacessibilidade e potencial antioxidante de compostos bioativos - Oliveira, Priscila Mayara de Lima (2019)
Ziziphus joazeiro Mart is a species that belongs to the Rhamnaceae family, endemic to the Caatinga, known for its pharmacological properties. The juazeiro fruits commonly known as “juá”, are globose drupes with a seed surrounded by a sweet and white mucilaginous pulp, being little consumed by the population. In the literature, studies were not found on the nutritional composition, phenolic compounds and antioxidant properties of juá. Therefore, a study is necessary to elucidate the knowledge about this fruit. In view of this, the present study aimed to characterize the fruit of juá collected in four mesoregions of Paraíba regarding its morphological aspects, physical-chemical and nutritional composition, profile and bioaccessibility of phenolic compounds by in vitro gastrointestinal digestion assays and antioxidant properties. Juá fruits were characterized by weight, longitudinal and transversal diameter. The nutritional and physical-chemical characterization was determined by the parameters of soluble solids, pH, moisture, crude protein, total lipids, ash and total fibers. The profile of sugars, organic acids and phenolic compounds were quantified by high performance liquid chromatography (HPLC). In vitro gastrointestinal digestion simulated stages of the oral (α-amylase), gastric (pepsin) and intestinal (pancreatin) phases coupled to a dialysis membrane to simulate the intestinal wall. The percentage of the dialized and non dialized fraction determined the bioaccessibility of phenolic compounds. The antioxidant activity of fruits and fractions of gastrointestinal digestion were evaluated by the methods of reducing capacity of Fe+ 2 (FRAP), capture of the radical DPPH • and ability to capture oxygenated radicals (ORAC). The results obtained were submitted to analysis of variance (ANOVA) and Tukey's test at the level of 5% (p ≤ 0.05). The juá fruits presented an ovoid shape, with better results in relation to the size and weight of the juá fruits from the Mata Paraibana (MP). The fruits of the different regions showed high moisture (65.33-72.53%), low acidity and succinic acid as the predominant organic acid. The analyzed fruits had a high content of dietary fibers (8.98 - 10.81%) with emphasis on insoluble fibers (5.72-0.02%). In relation to the phenolic compounds, the MP fruits showed the highest amounts of free phenolics (24.27 mg / 100g) and the highest antioxidant activity in the DPPH, FRAP and ORAC assays. In Agreste (AG) fruits, catechin (12.76 mg / 100g) was the major compound in the fraction of conjugated phenolics. The content of phenolic compounds varied among the fruits of the different regions. Catechin, epicatechin, epicatechin gallate, epigallocatechin gallate, procyanidin B1 and syringic acid were the most bioaccessible compounds. The fruits of the Sertão Paraibano (SP) showed higher bioaccessible phenolic content, as well highest antioxidant activity in all assay. The results revealed that the fruits of the different regions of Paraíba have differences in relation to the nutritional, morphological and physical-chemical characteristics confirming that the edaphoclimatic factors directly influence the chemical composition of the fruit, with high potential for consumption.